Long non-coding RNA AGER-1 inhibits colorectal cancer progression through sponging miR-182. Issue 1 (March 2020) - Lin, Mingzhu; Li, Yinyan; Xian, Jianfeng; Chen, Jinbin; Feng, Yingyi; Mao, Chun; Pan, Yujie; Li, Zhi; Zeng, Yuyuan; Yang, Lei; Lu, Jiachun; Wei, Yisheng; et al.
Objective: Abundant evidence has illustrated that long non-coding RNA (lncRNA) plays a vital role in the regulation of tumor development and progression. Ectopic expression of a novel lncRNA, termed lnc-AGER-1, has been discovered in cancers, and this lncRNA was reported to exert an anti-tumor effect. However, its biological mechanism remains unelucidated in colorectal cancer. Methods: A total of 159 paired colorectal cancer specimens and adjacent tissues was applied to detect the expression of lnc-AGER-1 by the quantitative Real-time PCR (qRT-PCR), and a series of functional assays was executed to uncover the role of this lncRNA on colorectal cancer. Results: We found that the expression of lnc-AGER-1 in the tumor tissues was significantly down-regulated, while compared with adjacent normal tissues (0.0115 ± 0.0718 vs. 0.0347 ± 0.157; P < 0.0001). Also, lnc-AGER-1 was observably associated with clinical T status (r = −0.184, P = 0.024). Patients with advanced T status exerted a significantly lower level of lnc-AGER-1 than those with early T status (20.0% vs. 40.7%, P = 0.021). Over-expression of lnc-AGER-1 inhibited cell proliferation and migration efficiency, and induced cell cycle arrest at the G0/G1 phase, and promoted cell apoptosis. Further research proved that lnc-AGER-1 altered the expression of its neighbor gene, AGER, through acting as a competing endogenous RNA for miR-182 in colorectal cancer. Conclusion: lnc-AGER-1 has a suppressive role in colorectal cancer development via modulating AGER, which may serve as a target for colorectal cancer diagnosis and treatment.